Evaluation of native avocados in the northern region of Nuevo León, Mexico - Acosta Díaz, Efraín; Almeyda León, Isidro Humberto; Hernández Torres, Ismael (Revista Mexicana de Ciencias Agrícolas, 2018)
The state of Nuevo León, Mexico, is part of the center of origin of the Mexican race of avocado (Persea americana Mill var. drymifolia). Avocado landraces are grown in the northern region, in commercial orchards and backyards, predominantly using the Pepe and Negro Santos varieties (local varieties). These varieties are characterized by having an intermediate and delayed cycle, respectively, according to the harvest season, which restricts the production of avocado in that region to a relatively short period. The purpose of this study was to characterize a group of native varieties of avocado from the northern region of the state of Nuevo León through the morphological characters of the fruits. We used 19 varieties, including the varieties Pepe and Negro Santos (local controls), present in two commercial orchards in the municipalities of Sabinas Hidalgo and Bustamante, Nuevo León. We determined seven materials with similar morphological characteristics to the varieties Pepe and Negro Santos and classified them into fourgroups.Thefirstgroupconsistedofavarietyoffruitwith characteristics similar to the Pepe variety and an early harvest period. The second group consisted of four fruit varieties with characteristics similar to the Pepe and Negro Santos varieties and an intermediate harvest period. The third group consisted of a variety with different fruit characteristics from the Pepe and Negro Santos varieties, an intermediate harvest period and green fruits. The fourth group consisted of a variety with fruit characteristics similar to the Pepe and Negro Santos varieties, with a late harvest period. The results suggest that there is a wide variation in the avocado landraces grown in the northern region of the state of Nuevo León, which allows the opportunity to diversify the production and not rely solely on the Pepe and Negro Santos varieties.
Keywords: Persea americana Mill.; genetic resources; landraces; morphological characterization